Exploring the potential link between ADHD, anxiety, autism, and cancer risk - Wajapeyee, Shreya; Ford, Kristina; Gupta, Romi (Frontiers in Oncology, 2025)
Neurodevelopmental and mental health disorders such as autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD), and anxiety disorders (AD) are increasingly being studied for their potential links to cancer risk. In this review, we present evidence indicating that ASD alone is not strongly associated with an increased risk of cancer. However, elevated risk is observed in subgroups with co-occurring intellectual disability or congenital anomalies. For ADHD, no direct biological link to cancer has been established, though behavioral factors and medication use remain areas of concern. Anxiety disorders may contribute indirectly to cancer risk through chronic stress and associated health behaviors, with some studies suggesting increased risk for specific cancers, such as prostate or urological cancers. Overall, this review highlights that increased cancer risk appears to be more closely related to co-occurring conditions and lifestyle factors than to the primary diagnoses themselves.